Chimeric features of Valeriy Shevchuk’s triptych “Three leaves outside the window” - Коноваленко, Тетяна Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the research problem of chimeric features of Valeriy Shevchuk’s novel “Three leaves outside the window”. The author studies the structural organization of the triptych, content connections of all three parts. The main characters of the novel are compared, their common peculiarities are emphasized; they are associated with some unusual abilities, life circumstances, connected with their life philosophy. Mythologems of the novel are described as important elements of building up the fiction reality and irreality. There is detailed analysis of the Good and the Evil, interweaved in the fates of all three characters and connected with the transparent message of the novel – finding out the sense of life.